Synthesis and characterization of nanocrystalline hydroxyapatite powder - Asmawi, R.; Ibrahim, M.H.I.; Amin, A. M.; Mustapha, N.; Sopyan, Iis (Trans Tech Publications, Switzerland, 2015)
Nanocrystalline hydroxyapatite (HA) powder was synthesized by a simple heating process involving simple chemical reaction. The characterization of the produced powder showed that the powder is nanosize with particle in the range of 30-70 mm in diameter and almost evenly spherical in shape. The powder also has a high surface area of 43.16 m2/g. Field Emission Scanning Electron Microscopy (FESEM) observation showed the crystallite and particle size become bigger with an increment of calcination temperature, indicating increasing of crystallinity. FESEM observation showed the particle size become bigger with an increment of calcinations temperature. It is in agreement with the crystallite size analysis, obtained by Scherer’s formula and particle size analysis, measured by Nano-Sizer. X-ray Diffraction (XRD) and Fourier Transform Infra Red Spectroscopy (FTIR) analyses exhibited the same result, where HA phase was clearly observed at at various temperatures up to 600˚C. However, at temperature more than 600˚C, Tri calcium phosphate (TCP) phase appeared suppressing the HA phase, producing biphasic calcium phosphate.